São Paulo: imagens, monumentos e a disputa pela memória - Santos, Samara Ferreira dos (2023)
The central objective of this work is to bring to academic debate a discussion about the struggle for memory in the city of São Paulo, starting from the incendiary action on the statue of the bandeirante Manoel Borba Gato in 2021. It considers all the repercussions stemming from this event and the attempt to criminalize a popular movement. Grounding the debate, the aim is to address the issue inherent in honoring dominators, highlighting the sense and meaning attributed to similar monuments. Simultaneously, there is a questioning of history education and the instrumentalization of symbols in the city's occupation through public policies for the preservation and conservation of the capital's memory.In this way, methodologically, it was intended to carry out a documentary analysis supported by literature reviews, testimonies, journalistic analyses, and the collection of empirical data to provide a foundation for reflecting on the proposed issues. This is done within the socio-political and theoretical perspective of the aforementioned events